Prefaces to Canon Law books in Latin Christianity. Selected Translations, 500-1245, New Haven, Connecticut, London 1998: [Rezension] - Sieger, Albert (De processibus matrimonialibus, 2004)
Kommentar und Übersetzung von Robert Sommerville und Bruce B. Brasington